The Determinant of Banking Efficiency in Indonesia (DEA Approach) - Sari, Putri Zanufa; Saraswati, Erwin (Journal of Accounting and Business Education, 2017)
This research is aimed to analyze efficiency performance in banking industries in Indonesia within 2012-2014 period. Data Envelopment Analysis method was used to find determinant in Tobit regression model. Purposive sampling was used to determine samples with the number of companies up to 89 banks consist of 5 different groups. Those are 26 state and local government own enterprises, 6 foreign banks, 11 mixed banks, 19 BUSN Devisa, 27 BUSN non Devisa. Based on analysis result, obtained that the foreign banks has the efficiency the highest compared to a group of banks BUMN/BUMD ( the government banks), BUSN non-foreign exchange , BUSN foreign exchange , and a group of banks a mixture. Efficiency in banking influenced by return on assets (ROA). The higher roa will be able to improve the efficiency banks in indonesia .Keywords: DEA, Tobit, ROA, CAR, NPL